Oncogenic and Tumor Suppressor Functions for Lymphoid Enhancer Factor 1 in E2a-/- T Acute Lymphoblastic Leukemia - Carr, Tiffany; McGregor, Stephanie; Dias, Sheila; Verykokakis, Mihalis; Le Beau, Michelle M.; Xue, Hai-Hui; Sigvardsson, Mikael; Bartom, Elizabeth T.; Kee, Barbara L. (Frontiers in Immunology, 2022)
T lymphocyte acute lymphoblastic leukemia (T-ALL) is a heterogeneous disease affecting T cells at multiple stages of their development and is characterized by frequent genomic alterations. The transcription factor LEF1 is inactivated through mutation in a subset of T-ALL cases but elevated LEF1 expression and activating mutations have also been identified in this disease. Here we show, in a murine model of T-ALL arising due to E2a inactivation, that the developmental timing of Lef1 mutation impacts its ability to function as a cooperative tumor suppressor or oncogene. T cell transformation in the presence of LEF1 allows leukemic cells to become addicted to its presence. In contrast, deletion prior to transformation both accelerates leukemogenesis and results in leukemic cells with altered expression of genes controlling receptor-signaling pathways. Our data demonstrate that the developmental timing of Lef1 mutations impact its apparent oncogenic or tumor suppressive characteristics and demonstrate the utility of mouse models for understanding the cooperation and consequence of mutational order in leukemogenesis.